Discovery of spirocyclic-diamine inhibitors of mammalian acetyl CoA-carboxylase. Issue 22 (15th November 2015) - Kung, Daniel W.; Griffith, David A.; Esler, William P.; Vajdos, Felix F.; Mathiowetz, Alan M.; Doran, Shawn D.; Amor, Paul A.; Bagley, Scott W.; Banks, Tereece; Cabral, Shawn; Ford, Kristen; Garcia-Irizarry, Carmen N.; et al.
Graphical abstract: Abstract: A novel series of spirocyclic-diamine based, isoform non-selective inhibitors of acetyl-CoA carboxylase (ACC) is described. These spirodiamine derivatives were discovered by design of a library to mimic the structural rigidity and hydrogen-bonding pattern observed in the co-crystal structure of spirochromanone inhibitorI . The lead compound3.5.1 inhibited de novo lipogenesis in rat hepatocytes, with an IC50 of 0.30 μM.